Programa "CSCJF" basado en la teoría de jean Piaget para mejorar las habilidades básicas del pensamiento Lógico Matemático en los niños de 5 años de la Institución Educativa Nº 00205 del distrito de Rioja. - Hernández Guevara, Nancy Rocío (2006)
The present investigation had had as objective to elaborate and to apply the program "CSCJF" to improve the basic abilities of the mathematical logical thought significantly in the children and girls of 5 years of the lnstitution Educational Nº 00205 of the district of Rioja; 1 study that is justified specifically for their relevance in the educational field in Logical Mathematics's area that you development in the level of initial education and to have allowed to stimulate in the children and girls the basic abilities that will be good them for the mathematical logical knowledge. The theoretical conception that sustains the present study is based on the contributions of Piaget (1975 - 1977), on the mathematical logical knowledge in the boy and in the studies of Riquelme (2003), on the basic abilities for the initiation to the calculation. Supported in these theories, it was considered the following hypothetical position: Alternative hypothesis; lf it is elaborated and does it apply the program "CSCJF" based on Jean's theory Piaget, then he/she will improve the basic abilities of the Mathematical Logical Thought significantly in the children and girls of 5 years of the lnstitution Educational Nº 00205 of the district of Rioja, 2006?. Null hypothesis; lf it is elaborated and it applies the program "CSCJF" based on Jean's theory Piaget, then he/she won't improve the basic abilities of the Mathematical Logical Thought in the children and girls of 5 years of the lnstitution Educational Nº 00205 of the district of Rioja, 2006. The sample was conformed by 20 children and girls of the lnstitution Educational lnitial Nº 00205 of the district of Rioja, the age of the children and girls it is of 5 years, to this sample he/she was applied the program of basic abilities "CSCJF" during 9 days. After the analysis and respective interpretation of the results, it was demonstrated that the application of the program "CSCJF" improves the basic abilities of the mathematical logical thought significantly in the children and girls of 5 years of the lnstitution Educational Nº 00205 of the district of Rioja.